Logitech / Muhammad Isyraf Hasri - Hasri, Muhammad Isyraf (2022)
Logitech International S.A. often shortened to Logi is a Swiss-American manufacturer of computer peripherals and software, with headquarters in Lausanne, Switzerland and Newark, California. The company has offices throughout Europe, Asia, Oceania, and the Americas, and is one of the world's leading manufacturers of input and interface devices for personal computers (PCs) and other digital products. The company develops and markets personal peripherals for PC navigation, video communication and collaboration, music and smart homes. The company include in manufacturing products like keyboard, mice, tablet accessories, webcam, Bluetooth speakers, universal remotes and many more. A Swiss company focused on innovation and quality, Logitech designs products and experiences that have an everyday place in people's lives. Logitech started connecting people through innovative computer peripherals and many industry firsts, including the infrared cordless mouse, the thumb-operated trackball, the laser mouse, and more. Since those early days, they have expanded both their expertise in product design and global reach. For each of products, they focus on how customers connect and interact with the digital world. By keeping design at the center of everything they have created, in every team and every discipline, to create truly unique and meaningful experiences. With products sold in almost every country in the world, Logitech has developed into a multi-brand company designing products that bring people together through music, gaming, video and computing. Brands of Logitech include Logitech, Logitech G, ASTRO Gaming, Ultimate Ears, Jaybird, Blue Microphones, and Streamlab